2020
DOI: 10.15586/jptcp.v27i1.666
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the effects of sugar-sweetened beverages on human health: A key global health issue

Abstract: The provision of healthy and safe food is vital for human health, and the addition of unnecessary sugars in foodstuffs is an important global issue, leading to multiple long-and short-term health issues and spiraling costs for individuals and governments alike. The negative effect of excess sugar consumption contributes to adverse health conditions, including obesity, type 2 diabetes, and poor oral health in both high and low resource settings. A key plank of governmental and health promotion bodies' nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 193 publications
0
32
0
1
Order By: Relevance
“…Sucrose has been, traditionally, the most popular sweetener. However, the negative effects of excess sucrose consumption, such as type 2 diabetes, obesity, and poor oral health, has led to the replacement of sugar by sugar alcohols [ 51 ]. Sugar and sugar alcohols are believed to be kosmotropic substances that stabilize the native structure of biopolymers, including starch [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sucrose has been, traditionally, the most popular sweetener. However, the negative effects of excess sucrose consumption, such as type 2 diabetes, obesity, and poor oral health, has led to the replacement of sugar by sugar alcohols [ 51 ]. Sugar and sugar alcohols are believed to be kosmotropic substances that stabilize the native structure of biopolymers, including starch [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that patients with epilepsy also showed a lower serum concentration of 25(OH)D3. In this study, epilepsy patients were more likely to consume sugar-sweetened soda, which, due to the content of sugar, preservatives, and dyes, are considered less bene cial to health [41].…”
Section: Discussionmentioning
confidence: 84%
“…Increasing consumption of snacks and sugar-sweetened beverage consumption during online gaming or watching movies online [18] may also result in excess fat accumulation [17]. In addition, increasing computer usage contributes to obesity in households in other LMICs,…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also found that prolonged internet usage (3 hours or more a day) and internetbased recreational activities, including watching online movies, reading newspapers, playing games, and watching television, are positively associated with BMI among adolescents and adults [13][14][15][16]. In addition, there is evidence that greater use of electronic devices for online gaming and social networking leads to increased consumption of sugar-sweetened beverages [17] and, therefore, overweight and obesity [18].…”
Section: Introductionmentioning
confidence: 99%